2019
DOI: 10.14393/bj-v35n3a2019-42070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lysinibacillus SP, isolated from Coptotermes curvignathus Gut, for the delignification of oil palm residues

Abstract: The application of ligninolytic bacteria and enzymes is a green pre-treatment alternative in the production of paper and biofuel from oil palm residues. In this study we investigated the ability of Lysinibacillus pakistanensis isolated from termite gut in degrading the lignin component of oil palm residues. The residues were biotreated with the bacterial strain in an aerated submerged fermentation system for 7 days at 30 , pH 7 and compared with untreated control. Enzyme activities were determined using specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Genera that may contain large amounts of probiotics, such as Lactobacillus and Enterococcus , were enriched in the colon of FAM pigs. Interestingly, Lysinibacillus , a genus with a strong ability to degrade lignocellulose ( Ayeronfe et al, 2019 ), was also found more abundant in pigs fed FAM diet. It is speculated that the changed microbiota in colon of FAM pigs contributed to the fermentation ability more than CON pigs, which was confirmed by the markedly higher concentration of acetate in the colon of these pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Genera that may contain large amounts of probiotics, such as Lactobacillus and Enterococcus , were enriched in the colon of FAM pigs. Interestingly, Lysinibacillus , a genus with a strong ability to degrade lignocellulose ( Ayeronfe et al, 2019 ), was also found more abundant in pigs fed FAM diet. It is speculated that the changed microbiota in colon of FAM pigs contributed to the fermentation ability more than CON pigs, which was confirmed by the markedly higher concentration of acetate in the colon of these pigs.…”
Section: Discussionmentioning
confidence: 99%